Bargaining, openness and the labor share - Dorothee Schneider (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This paper investigates determinants of changes of the labor share in developed countries with a focus on Western Europe. Using a country-industry panel that covers the private sector, the paper focuses on long and short-run changes within industries. The results show a large and time-persistent impact of increasing globalization on the labor share, especially if the within-industry changes are considered. Openness seems to be the driving force for downward movements in the industry level labor shares while technological and institutional forces impact these shares positively. Furthermore, while investments into information and communication technology (ICT) increase productivity of workers, it has a negative impact on the labor share as it enables higher economic integration which lowers the labor share. Economic integration has stronger impact on the polarization in Western European labor markets than ICT.
Keywords: E25; J23; F16; O33; E02; 330; labor share; functional income distribution; openness; Lohnquote; Funktionelle Einkommensverteilung; Globalisierung; Informationstechnik; Lohnverhandlungstheorie; Verhandlungsmacht; Schätzung; Westeuropa